PENGARUH PROMOSI TERHADAP KEPUTUSAN MUZAKKI MEMBAYAR ZAKAT DENGAN KEPERCAYAAN DAN PENGETAHUAN SEBAGAI VARIABEL INTERVENING DI LEMBAGA AMIL ZAKAT INFAQ DAN SHADAQAHMUHAMADIYAH (LAZISMU) SUMATERA SELATAN - Asiati, Diah Isnaini (PRIMA EKONOMIKA, 2022)
Zakat is a financial axis in Islam. With a Moslem majority population, Indonesia should be able to collect and manage zakat funds properly in order to improve the welfare of the society. However, zakat management is considered less than optimal for all this time. The aim of this study was to determine the effect of promotion on the decision of muzakki for paying zakat with trust and knowledge as intervening variables. The research was designed associatively. The variables used are promotion, trust, and knowledge, which are associated with the decision for paying zakat. The research population was 100 muzakki in Lazismu Palembang which were taken by purposive sampling. The data used is primary data with collection techniques through questionnaires. Furthermore, the analysis technique used is path analysis. The results of the study prove that 1) promotion, trust, and knowledge, have a significant effect on the decision of muzakki for paying zakat; 2) promotion has a significant effect on the decision of muzakki for paying zakat, but trust has no significant effect on the decision of muzakki for paying zakat; and 3) promotion has a significant effect on knowledge and as well as knowledge on the decision of muzakki for paying zakat.